Análisis de las debilidades del sistema de Bodega de la UTB, para mitigar las falencias en sus procesos. - Diaz Cabrejo, Rafael Gregorio (2017)
At present it is possible to be observed that a large number of companies and micro-enterprises are advancing by leaps and bounds and feel the need to employ new technologies that help them in the automation of certain manual processes that in many cases become tedious and complicated, show the expected results in the set time. It is of great importance to point out that the development that has reached the technology in these times is of great help for the companies in general, through the use of the different computer tools. One of the main problems that arises in many of the departments that deliver materials in the main companies or institutions; is the lack of the equipment or technological material necessary to perform a good control in these departments, since these technological equipment allows to handle many processes that to some extent become complicated when they are done manually. So it is that the Department Warehouse Warehouse of the Technical University of Babahoyo, has a small computer system that is basic and limited to develop the different activities and processes that are handled in this department. His name is Kardex Taurus, which is hardly used in the department because it does not fully fulfill the expectations it projected.